Main stages of the development of the specialty "Orthopedics and traumatology" - Bodnya, A. (Journal of Education, Health and Sport, 2022)
The most significant components of the educational process at the Department of Traumatology and Orthopedics of the Odessa National Medical University (Ukraine) under modern conditions are highlighted. Purpose: To determine the future orthopedist-traumatologist professional training main stages, including the means of implementing the development of the specialty. Materials and methods. The specific conditions of the specialty "Orthopedics and Traumatology" development under certain circumstances (COVID-19 pandemic; martial law) in the phased professional training of specialists. The following empirical methods were used: observation, test, questionnaire method and method of conversation and interview. Results: It has been determined that there is a significant difference between full-time and distance/on-line learning for higher education applicants, since most clinical competencies require the personal presence of a doctor. It is live contact at the bedside of the patient, as well as with the staff of the in - patient departments and colleagues of the chairs will create a situation of real professional growth, which cannot be replaced by any virtual technology of a specialty practical mastery. Conclusions: The main stages of education affect the development of the specialty, depending on the pace and body of acquired knowledge and skills. The professional qualities of an orthopedist- traumatologist are subject to education by all available methods and means, starting from the student bench of a medical university. Further deepening and improvement of knowledge and skills should continue until the end of one’s professional activity, especially in difficult and unforeseen situations.